2017
DOI: 10.18632/oncotarget.22682
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HPV related oropharyngeal cancer in oral rinse specimens

Abstract: BackgroundThe majority of patients diagnosed with oropharyngeal squamous cell cancer (OPSCC) are due to HPV infection. At present, there are no reliable tests for screening HPV in patients with OPSCC. The objective of this study was to assess the Cobas® HPV Test on oral rinse specimens as an early, non-invasive tool for HPV-related OPSCC.MethodsOral rinse specimens were collected from 187 patients (45 with OPSCC, 61 with oral cavity SCC (OCSCC) and 81 control patients who had benign or malignant thyroid nodule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…It demonstrates that a screened individual can receive significantly less morbid treatment than would be required for the standard presentation at a more advanced stage. This report and previous studies (8,11,12,22), support the value of a salivary oral rinse test as a potential screening tool. Unlike previously published work, our study is the first to demonstrate that continuous monitoring of HPV-16 DNA in salivary oral rinse samples can detect occult OPC.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It demonstrates that a screened individual can receive significantly less morbid treatment than would be required for the standard presentation at a more advanced stage. This report and previous studies (8,11,12,22), support the value of a salivary oral rinse test as a potential screening tool. Unlike previously published work, our study is the first to demonstrate that continuous monitoring of HPV-16 DNA in salivary oral rinse samples can detect occult OPC.…”
Section: Discussionsupporting
confidence: 81%
“…Salivary oral rinse samples of this individual were collected at baseline, 6, 12, 36 month, and 2 weeks after his bilateral tonsillectomy using previously published method (8)(9)(10). Briefly, participants were asked to swish and gargle for 1-2 min with 2 × 10 mL volumes of 0.9% saline, prior to expectorating the rinse sample into a 50 mL falcon tube.…”
Section: Clinical Specimens' Collection and Processingmentioning
confidence: 99%
“…Tumor HPV status was determined by p16 IHC and/or HPV DNA ISH on tumor samples and PCR amplification of 37 different subtypes of HPV was performed on oral rinses. The authors concluded that the oral rinse test had a sensitivity of 72.2% and a specificity of 90%, similar to prior studies [72]. One publication has shown conflicting results regarding the utility of HPV detection in saliva, but definitive conclusions may be difficult to draw due to small sample size in that case-control study [73].…”
Section: Salivary Hpv Dnasupporting
confidence: 63%
“…7 Importantly, an HPV mRNA evaluation represents the gold standard for identifying HPV-driven HNC because HPV DNA alone does not prove an HPVassociated etiology of the tumor. 3,8 Because of the simple and noninvasive nature of their collection, oral rinses and gargles (hereafter called oral rinses) have been used to search for a variety of HPVassociated biomarkers, such as HPV DNA [9][10][11][12][13][14] and HPVspecific antibodies, 15,16 in both healthy subjects and patients with HNC. In contrast, HPV mRNA detection in oral specimens is very challenging because mRNA is highly susceptible to degradation by the enzymes present in oral fluids.…”
Section: Introductionmentioning
confidence: 99%